Disclosing Racism in Racial Roles in the Novel Interior Chinatown by Charles Yu (Sastra Inggris UNPAM, 2024)
This research is the crucial issue about racial discrimination that can be found in society in some countries. The purposes of this research is to analyze the depiction of racial discrimination faced by Willis Wu and to uncover the form of racial discrimination experienced by Willis Wu in the Interior Chinatown novel (2020) written by Charles Yu. The story of the novel portrays about an American actor of Taiwanese descent as the reflection of real social conditions about racial discrimination in the United States of America. It is presenting the inequality treatment that leads to a discriminative attitude based on a different race through the Colored and looks. It has negative consequences for those who are subjected to them, such as a loss of self-confidence, a negative self-image, and a great deal of resentment. Those who have been treated unfairly will rarely accept their fate; instead, they will fight back. The method used to analyze the data is qualitative approach. And the theory of Fred L. Pincus (1996) and the theory of Homi K. Bhabha (1994) are used to support the concept of those related explanations about the racial discrimination issue. In getting data there are some steps used first, reading the novel several times. Second, finding the data relate to the issue. Next, classifying the data based on an analysis. The last, analyzing the data finding based on the theory.